Metode Pembinaan Keagamaan dalam Meningkatkan Ketenangan Jiwa Warga Binaan - Nuriyaratri, Amelia; Setiana, Wiryo; Marlina, Elly (Irsyad: Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2024)
The purpose of this study was to determine the religious development of the inmates through the Shalihah pesantren program at the Class IIA Sukamiskian Women's Prison in Bandung, the method of religious development in increasing the peace of mind of the inmates, and the results of the religious guidance method in increasing the peace of mind of the inmates through the Shalihah pesantren program. descriptive method with a qualitative approach. Data collection methods in the form of observation, interviews, documentation. Based on the results of the research conducted, the religious guidance carried out at the Class IIA Sukamiskin Women's Penitentiary in Bandung has mentors who help the inmates in experiencing the anxiety that exists in themselves. This religious development is carried out through the shalihah pesantren program.